Demographic and clinical characteristics of patients presenting with conversion disorder in a tertiary care hospital in north India - Ismail, Haamid; Qadri, Sabreena; Hussain, Arshad; Ismail, Nadia (International Journal of Research in Medical Sciences, 2021)
Background: Conversion (functional neurological symptom) disorder refers to patients who have neurological symptoms in the absence of neurological disease, encompassing one or more symptoms of altered voluntary motor or sensory function. Aim of the study was to study the demographic and clinical characteristics of patients with conversion disorder. Methods: The study population comprised all the patients (both inpatients and outpatients) of conversion disorder attending department of psychiatry, government medical college Srinagar over a period of 6 months who fulfilled the inclusion criteria of the study were evaluated on a semi-structured proforma for demographic variables and clinical characteristics. Results: A total of 76 patients of conversion disorder were included in our study. Conversion disorder is more common in age group of 20-29 years (52.6%), females (93.4%) and among students (71.1%) belonging to rural background. Motor symptoms were the predominant presentation with pseudo seizure (69.7%) being the commonest. A majority of the patients had an obvious psychosocial stressor, of which family-related (36.8%) and relationship- related (15.8%) problems accounted for the major types. Conclusions: Conversion disorders are commonly seen in young adult females, students and in those from rural background. They are mostly preceded by psychosocial stressors.